Productivity improvement in a canned fish production company applying 5S, TQM, and three pillars of TPM tools - Escobal Cordova, Maria Del Pilar (2025)
Lean Manufacturing concepts have been widely applied in manufacturing companies; however, there are limited instances of their use in the canned food sector. Consequently, there is a need for techniques that can sustain efficiency and productivity over time. This research aims to enhance the productivity of an SME that produces canned fish by implementing 5S, TQM, and the three pillars of TPM. Using the DMAIC methodology, a thorough diagnosis of the company was conducted to identify the root causes of its main issues. Lean tools were then tested in a pilot program within the organization. Following the implementation, improvements were observed in the company's key performance indicators. This demonstrates the effectiveness of the management model, showcasing the positive impact of these tools when applied in a food industry context, and contributing to the existing body of knowledge on the subject.